Pengaruh Kualitas Pelayanan dan Kepuasan terhadap Loyalitas Pelanggan GoFood di Gojek pada Mahasiswa Fakultas Ekonomi Universitas Mercu Buana Yogyakarta - Wulan Intan Ihatal Janah; Zaenal Wafa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Go-Food is a feature in the Gojek application with food delivery services. Researchers aim to determine the influence of Go-Food quality on the loyalty given and the influence of satisfaction on the loyalty given to students. Researchers used questionnaires in collecting data. The samples used were taken by random sampling, where samples taken from the population were carried out irregularly. Research methods for processing data are: validity test, reliability test, and classical assumption test. In the classical assumption test, researchers used the Normality Test, multicollinearity test, and heteroscedasticity test. Then this researcher used multiple regression analysis, coefficient of determination and hypothesis testing which used the f test and t test. The results of the research conducted were that service quality and satisfaction partially had a positive and significant effect on customer loyalty.